The replication activation potential of selected RNA polymerase II promoter elements at the simian virus 40 origin. - Hoang, A T (1992)
Binding sites for cellular transcription factors were placed near the simian virus 40 origin of replication, and their effect on replication and TATA-dependent transcription was measured in COS cells. The hierarchy of transcriptional stimulation changed when the plasmids replicated. Only one of seven inserted sequences, a moderately weak transcription element, stimulated replication detectably. However, when two nonstimulatory sites were present in multiple copies they did activate replication. Multiple sites for the chimeric activator GAL4-VP16 did not stimulate replication even though transcription was stimulated strongly. The results indicate that the ability of a binding site to stimulate replication from the simian virus 40 ori is not based on its transcriptional activation potential but is instead related to a separate replication activation potential that can be increased by having multiple sites.